RESOLUTION OF THE ROUND TABLE DISCUSSION WITH EXPERTS IN EPILEPSY AND HEALTH MINISTRY EXECUTIEVES (FROM THE KHABAROVSK REGION, THE LENINGRAD REGION, THE SAMARA REGION, THE IRKUTSK REGION, AND THE TYUMEN REGION) ON THE ALL-RUSSIAN MEDICAL AND SOCIAL PROJECT "ATTENTION – EPILEPSY!" - article Editorial (Эпилепсия и пароксизмальные состояния)
.